Pengaruh Pengetahuan, Budaya Dan Dukungan Suami Terhadap Pengambilan Keputusan Alat Kontrasepsi: The Effect of Knowledge, Culture, and Husband's Support on Contraceptive Device Decision Making - hat, futi (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Family planning programs have a major impact on population growth, both quantitatively and qualitatively. Strengthening the use of contraceptives aims to reduce dropouts and prevent the increase in the incidence of unwanted pregnancies and the possibility of a "baby boom". The reluctance to use contraception according to the 2017 Indonesian Demographic and Health Survey is mostly due to fear of side effects, methods that are not suitable for them, and also because they do not get the husband's approval. The purpose of this study was to determine the effect of knowledge, culture, and husband's support on the decision-making of the choice of contraceptive method.  Methods: Quantitative research methods collect data by distributing research questionnaires, sampling technique using simple random sampling, data analysis using multivariate follow-up analysis using logistic regression, and simultaneous testing.  Results: From the test results there is a significant effect between the knowledge variable with a p-value of 0,033. Culture p-value 0,014 and husband's support p-value 0,033 because the p-value is less than 0,05. Simultaneously there is an influence between the variables of knowledge, culture, and husband's support on decision making. With a calculated F value of 2,863, it is greater than F table 2,70 and a sig value of 0,041 is less than 0,05.  Discussion: The influence of these three variables on contraceptive decision making because good knowledge, a supportive culture, and full support from the husband will make the acceptor or respondent feel comfortable using contraception and make the right decision in choosing the contraceptive used.